Who Benefits from Better Roads and Why? Mixed Methods Analysis of the Gender-Disaggregated Impacts of a Rural Roads Project in Vietnam - Mannava, Aneesh; Perova, Elizaveta; Tran, Phuong Thi Minh (World Bank, Washington, DC, 2020)
The literature lends empirical support for the idea that improvements to transport infrastructure lead to economic development. How and why the benefits of better transport differ between genders is less clear. This paper attempts to answer this question by combining a nonexperimental impact evaluation of a large-scale rural roads project in Vietnam with qualitative data collection. The paper finds that roads improve economic opportunities for agricultural production and trade: all households increase agricultural trade. Yet only households headed by men capitalize on these opportunities, experiencing an increase in agricultural output and income. Production and income do not increase in households headed by women. The result seems to be driven by a lower level of household labor and access to capital in female-headed households, which constrains their ability to make up-front investments to increase production and income. Overall, the results indicate that female-headed households face constraints in taking advantage of newly created economic opportunities. Coordinating transport investments with complementary development programs addressing these constraints can improve the benefits of better transport for such households.